Peran Organizational Citizenship Behavior dalam Memoderasi Pengaruh Work Life Policies, Pemberdayaan, dan Training & Development Terhadap Kinerja - Willda Mega Ayudia; Suhartini Suhartini (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This research aims to examine the role organizational citizenship behaviour (OCB) in moderating the influence of work life policies (WLP), empowerment and training and development (T&D) on performance. In this research, the respondents are 40 employees of Industry and Trade Office of Tasikmalaya Regency. The data collection method uses a questionnaire. The analytical method uses regression analysis and path analysis. The result of this research denoted that: Firstly, WLP, empowerment and T&D positively and significantly affected the employees’ OCB both partially and simultaneously. Secondly, WLP, empowerment and T&D positively and significantly affected the employees’ performance both partially and simultaneously. Thirdly, OCB positively affected the employees’ performance. Fourthly, WLP, empowerment and T&D indirectly affected employee’s performance through OCB. All in all, the researcher expects that this research may be used as reference by Industry and Trade Office of Tasikmalaya Regency in order to improve the employees’ performance.